Matices En La Multitud: Proyecto Gráfico Para La Sensibilización De Las Personas Lgbtiq+ O Con Sexualidades Diversas Y Disidentes. (2023)
d is a project created from a place of enunciation itself as a person who feels diverse, loves diverse and interacts diverse from a sexuality different from heterosexuality, which is why through the journey that has been this exploration coupled with the experience of graphic design, is created a palette of colors that is traced by emotions and responds to the questions, What spaces are safe for LGBTIQ+ people in the locality of Uribe Uribe?, how to approach young people from 14 to 28 years old, to raise awareness and empathize with diverse and dissident sexualities, since the diversity of the locality is immense and the LGBTI House of the south zone, Amapola Jones, responsible for providing safe spaces for people of the LGBTIQ+ sectors is positioned as one of the first houses in the locality of Rafael Uribe Uribe to be created with an organized process by the government to provide assistance and ensure LGBTIQ+ rights.